PERLINDUNGAN HUKUM TERHADAP PT. DAYA GEMILANG INDONESIA ATAS PEMBELIAN FIKTIF BERDASARKAN PASAL 6 UNDANG-UNDANG PERLINDUNGAN KONSUMEN NOMOR 08 TAHUN 1999 - Widodo, Aris; Ratnawati, Elfrida (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Technological advancements have catalyzed a shift in buying and selling practices, ushering in the e-commerce era that enables online transactions anytime, anywhere. Despite the opportunities and conveniences offered by e-commerce, the practice of 'hit and run' by consumers, where goods are ordered without payment, has garnered attention. This has led to financial losses for business owners. The focus of this study is to comprehend the legal safeguards available to business owners against 'hit and run' consumer behaviors in online transactions. Through this research, a detailed examination will be conducted on the legal grounds that business owners can utilize to take legal action against consumers who violate contracts through 'hit and run' tactics. The research methodology employed is normative, utilizing a literature review approach. Research data is sourced from relevant regulations, particularly Law Number 8 of 1999 concerning Consumer Protection (UUPK). The objective of this research is to assess the legal protection afforded to business owners in online buying and selling transactions. The analysis centers on the rights of business owners as delineated in the UUPK and the legal justification for business owners to pursue legal action against consumers.Keywords: E-commerce, Consumers,Legal Protection, Breach of Contract,Buying and selling